Kaposi's sarcoma herpesvirus K15 protein contributes to virus-induced angiogenesis by recruiting PLCγ1 and activating NFAT1-dependent RCAN1 expression. - Kiran Bala (Public Library of Science (PLoS), 2012)
Kaposi's Sarcoma (KS), caused by Kaposi's Sarcoma Herpesvirus (KSHV), is a highly vascularised angiogenic tumor of endothelial cells, characterized by latently KSHV-infected spindle cells and a pronounced inflammatory infiltrate. Several KSHV proteins, including LANA-1 (ORF73), vCyclin (ORF72), vGPCR (ORF74), vIL6 (ORF-K2), vCCL-1 (ORF-K6), vCCL-2 (ORF-K4) and K1 have been shown to exert effects that can lead to the proliferation and atypical differentiation of endothelial cells and/or the secretion of cytokines with angiogenic and inflammatory properties (VEGF, bFGF, IL6, IL8, GROα, and TNFβ). To investigate a role of the KSHV K15 protein in KSHV-mediated angiogenesis, we carried out a genome wide gene expression analysis on primary endothelial cells infected with KSHV wildtype (KSHVwt) and a KSHV K15 deletion mutant (KSHVΔK15). We found RCAN1/DSCR1 (Regulator of Calcineurin 1/Down Syndrome critical region 1), a cellular gene involved in angiogenesis, to be differentially expressed in KSHVwt- vs KSHVΔK15-infected cells. During physiological angiogenesis, expression of RCAN1 in endothelial cells is regulated by VEGF (vascular endothelial growth factor) through a pathway involving the activation of PLCγ1, Calcineurin and NFAT1. We found that K15 directly recruits PLCγ1, and thereby activates Calcineurin/NFAT1-dependent RCAN1 expression which results in the formation of angiogenic tubes. Primary endothelial cells infected with KSHVwt form angiogenic tubes upon activation of the lytic replication cycle. This effect is abrogated when K15 is deleted (KSHVΔK15) or silenced by an siRNA targeting the K15 expression. Our study establishes K15 as one of the KSHV proteins that contribute to KSHV-induced angiogenesis.